Matrix synthesis and degradation in human intervertebral disc degeneration. (20th July 2007) - Le Maitre, C.L.; Pockert, A.; Buttle, D.J.; Freemont, A.J.; Hoyland, J.A.
Abstract : Degeneration of the intervertebral disc has been implicated in chronic low back pain. Type II collagen and proteoglycan (predominantly aggrecan) content is crucial to proper disc function, particularly in the nucleus pulposus. In degeneration, synthesis of matrix molecules changes, leading to an increase in the synthesis of collagens type I and III and a decreased production of aggrecan. Linked to this is an increased expression of matrix-degrading molecules including MMPs (matrix metalloproteinases) and the aggrecanases, ADAMTS (a disintegrin and metalloprotease with thrombospondin motifs) 1, 4, 5, 9 and 15, all of which are produced by native disc cells. Importantly, we have found that there is a net increase in these molecules, over their natural inhibitors [TIMP-1 (tissue inhibitor of metalloproteinases-1), 2 and 3], suggesting a deregulation of the normal homoeostatic mechanism. Growth factors and cytokines [particularly TNFα (tumour necrosis factor α) and IL-1 (interleukin 1)] have been implicated in the regulation of this catabolic process. Our work has shown that in degenerate discs there is an increase in IL-1, but no corresponding increase in the inhibitor IL-1 receptor antagonist. Furthermore, treatment of human disc cells with IL-1 leads to a decrease in matrix gene expression and increased MMP and ADAMTS expression. Inhibition of IL-1 would therefore be an important therapeutic target for preventing/reversing disc degeneration.